POTENTIAL VALUE-ADDED MINERALS IN FORMER NICKEL ORE MINING AREAS IN BATU PUTIH SUBDISTRICT, NORTH KOLAKA REGENCY: POTENSI NILAI TAMBAH MINERAL IKUTAN DI AREA BEKAS PENAMBANGAN BIJIH NIKEL DIKECAMATAN BATU PUTIH KABUPATEN KOLAKA UTARA - AGRIAL S., MUHAMMAD; Nafiu, Wd. Rizky Awaliah (INTAN Jurnal Penelitian Tambang, 2024)
Nickel is a natural metallic element predominantly found in the Earth's lithosphere. The escalating demand for the resources, especially in industrial development, has made the mining sector a major contributor to the supply of raw materials. The prices and demand for certain commodities increase the economic viability of previously unexploited mining locations. Therefore, abandoned mining sites have regained interest due to their remaining potential for the re-extraction of the resources. This research was carried out in the former nickel ore mining area in the Batu Putih area of ​​North Kolaka using observational and grab sampling methods, followed by X-ray fluorescence (XRF) analysis. The results showed that Ni levels in the samples ranged from 1.27%–1.67%, Fe between 12.03%–19.78%, Co between 0.02%–0.05%, and Al₂O₃ between 2.00%– 3.99%. Even though these three metals have economic potential, they cannot optimally proceed due to regulatory limitations. Estimates of the economic value of metals based on tonnage assumptions show Fe reaching 404,028 USD (1.5 million tons), Co reaching 16,631,208 USD (1.5 million tons), and Al₂O₃ reaching 20,827,800 USD (1.5 million tons). Developing comprehensive regulations is needed to support the sustainable management of these metals.